Relationship Between Number Of Involved Coronary Artery With Some Risk Factors By Angiography - Seyed Abedein Hosseini; Ali Akbar Abdollahi; Naser Behnampour; Aref Salehi (Tehran University of Medical Sciences, 2013)
Background and Aim: Despite the information regarding CAD risk factors, there isn't agreement between the relation of this risk factors and coronary artery diseases. This study was done for determination of related factors with vessels involved in coronary artery angiography. Materials and Methods: In this descriptive and analytical study, 2390 patients' .were selected via census sampling from Kosar Angiography center in the Golestan province. Data gathering form included data such as age, gender, body mass index (BMI), blood pressure, diabetes, smoking and opiates addiction history. Vessels involved were determined by angiography. Data analysis was done with one way ANOVAs and logistic regression using SPSS 16 soft ware. Results: Mean and standard deviation of patient's age was 57.9±10. 58.2 percent of them were male. There were significant correlations between age, gender and BMI with numbers of vessels involved. Male gender(OR=1.329), hypertension (OR=1.25) and diabetes(OR=1.20) increased the probability of more than one vessels involvement. Regression analysis showed there were no significant correlations between age, BMI, smoking and opiates addiction history with more than one vessels involvement. Conclusion: Our finding confirmed that male gender, hypertension and diabetes are the main risk factors in involvement of more than one vessel.